6x+2(3-x)-26=100

Simple and best practice solution for 6x+2(3-x)-26=100 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+2(3-x)-26=100 equation:


Simplifying
6x + 2(3 + -1x) + -26 = 100
6x + (3 * 2 + -1x * 2) + -26 = 100
6x + (6 + -2x) + -26 = 100

Reorder the terms:
6 + -26 + 6x + -2x = 100

Combine like terms: 6 + -26 = -20
-20 + 6x + -2x = 100

Combine like terms: 6x + -2x = 4x
-20 + 4x = 100

Solving
-20 + 4x = 100

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 4x = 100 + 20

Combine like terms: -20 + 20 = 0
0 + 4x = 100 + 20
4x = 100 + 20

Combine like terms: 100 + 20 = 120
4x = 120

Divide each side by '4'.
x = 30

Simplifying
x = 30

See similar equations:

| n-8=-16 | | 4/5n=0 | | 1/2t=5/14 | | d+3/5=27/20 | | n+5/8=85/8 | | x*8=171 | | -9+m=-10 | | 4a=16/5 | | k-8=0 | | 17/3=t-1/3 | | m/-3=5 | | n+3/4=21/20 | | b+7=43/7 | | n/9=8 | | b+1/2=-3/10 | | 26/3=d+2/3 | | 2+w=20/9 | | -131/12=t-10 | | k+1/9=-22/45 | | 6d=18/11 | | n+6=-6 | | 3/10+a=29/30 | | n+1=5/4 | | 4/7d=40/7 | | 19/6=d+1/6 | | n+3/8=75/8 | | 8=d+1 | | -1/33=b-2/3 | | x-7/8=-3/8 | | -4/5=d+1/5 | | a+6=63/10 | | 1/2+b=9/2 |

Equations solver categories